Appraisal Analysis of Western and Eastern Ministers Discourse in Al Jazeera News - Hussein Abdulameer, Ali; Noor Fazelah Mohd Noor, Siti; Abdul Latiff, Azmi (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to describe and analyze Eastern and Western ministers Attitudes towards the announcement by US President Donald Trump on December 6, 2017, in which his decision about the recognition of the US administration of Jerusalem as the capital of Israel, in the discourse using the Appraisal System Analysis. The discourse analysis was done by breaking down the discourse into several sentences and analyzing them to find out the Appraisal Devices and the types of Attitudes used. Analyzing the data, it could be inferred that the speech employed three kinds of Attitudes; Affect, Judgment, Appreciation. There were 55 clauses consist of 10 Affects, 4 Judgments, and 41 Appreciations. The findings reveal that negative Appreciation is most commonly attributed to the Trump’s decision on Jerusalem by the Eastern ministers and on the other hand Western ministers appraised the decision with positive Appreciation in Al Jazeera news which point to which ministers concern with Trump’s behavior and the objective world rather than with the emotional field.